Comparison of Istanbul-Ankara High Speed Train and Airplane and Automobile Passenger CO2E Emissions in Sustainability Assessment - Ozturk, Hakan N. (SPRINGER INTERNATIONAL PUBLISHING AG, 2024)
Some of the important indicators within the scope of sustainability are harmful emissions, including carbon footprint. In the coming period, pricing policies in transport will become more rational and inclusive, taking into account environmental impacts and limited resources. In this study, the data of the main means of transport between the cities of Istanbul and Ankara are taken as reference. By analysing the relevant data, high-speed train, airplane and automobile modes of transport are compared. As a result of the analysis, it has been revealed that the CO2 emission of high-speed train is more acceptable in terms of sustainability compared to other modes of transport. In the sustainable transport policy approach, high-speed train seems to be the most efficient mode of transport today, both environmentally and economically with lower external costs compared to air and road transport.
Keywords: Sustainability; CO2 emission; Transportation modes; Healt effect of CO2; External cost; Carbon capture; Transportation